Genotyping Escherichia coli O157:H7 strains isolated from cattle and small ruminants in Fars province (Iran) using Enterobacterial Repetitive Intergenic Consensus PCR Analysis - Sedigheh Mokhtari; Yahya Tahamtan; Mohammad Kargar; Keyvan Tadayon; Elham Moazamian (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux)
Background: Shiga toxin-producing Escherichia coli (STEC) strains are bacteria that cause gastrointestinal illnesses in humans. The strain E. coli O157:H7 diarrhea, hemorrhagic colitis, and hemolytic-uremic syndrome in humans. Cattle and small ruminants are the main reservoirs of E. coli O157:H7. When shed in animal faeces, the bacteria can contaminate soil, water and food. Aim: We genotyped bacterial isolates and identified their genetic associations and source of origin in order to reduce the spread of infections and improve disease control. Methods: An Enterobacterial Repetitive Intergenic Consensus (ERIC) polymerase chain reaction (PCR) was used to determine the genetic relationships and potential cross-contamination among isolates. The genetic fingerprint patterns obtained from the isolates were compared to determine their genetic associations. A total of twenty-two E. coli O157:H7 isolates were identified from samples collected in carcasses and rectums of cattle, sheep, goats, and from fruit juice samples. SMAC agar supplemented with specific nutrients was used to selectively and differentially isolate E. coli O157:H7. The isolates were then subjected to ERIC-PCR using ERIC1 and ERIC2 primers. Results: The genetic relationships and potential cross-contamination among isolates were evaluated using the fingerprint patterns obtained. Their similarities ranged from 46% to 100%. Isolates from different hosts and sources exhibited similar patterns, indicating a high prevalence of specific clones in various hosts. The study revealed the genetic diversity of E. coli O157:H7 collected from identical sources. Conclusion: This study highlights the importance of genotyping and identifying the sources of E. coli O157:H7 strains. Understanding the genetic relationships and potential cross-contamination among isolates can help prevent the spread of infections and improve the efficacy of disease control.